A brief review of the literature for published Dual-Energy X-Ray Absorptiometry protocols for athletes - Dallman, J.; Herda, A.; Cleary, C. J.; Morey, T.; Diederich, A.; Vopat, B. G.; Vopa, L. M. (Sports Health: A Multidisciplinary Approach, 2024)
Context: Dual-energy x-ray absorptiometry (DXA) is widely known for its utility in diagnosing a patient with osteopenia or osteoporosis; however, its utility in evaluation of body composition and potential athletic performance was previously routinely overlooked. In recent years, athletic programs have begun employing this equipment during athlete screening. However, it is currently unknown how athletic programs are utilizing this information to guide an athlete`s training and health.